Pornography Use and Sexual Offending: An Examination of Perceptions of Role and Risk - Holt, Karen M. (International journal of offender therapy and comparative criminology, 2024)
Despite no definitive relationship between pornography and sexual offenses, there exists an assumption that use plays a role in the commission of sexual crimes and may increase risk of recidivism. This has led to the development of post-release restrictions on adult media for those convicted of a sexual offense. We conducted semi-structured interviews with 101 incarcerated individuals convicted of a sexual offense to explore the central research questions: (1) What are the common themes among individual’s experiences regarding pornography and how do they construct the role of pornography in their offending? (2) How do they frame pornography use post-release and understand pornography use as related to risk of re-offense? A qualitative analysis revealed common themes regarding how individuals constructed pornography use and notions of risk. Strategic and targeted monitoring and supervision of those who perceive their pornography use as consuming and facilitating may be a more effective practice than abstinence-only blanket restrictions.